Social insurance and retirement: A cross-country perspective - Tobias Laun; Johanna Wallenius (Stockholm School of Economics, The Economic Research Institute (EFI), 2013)
In this paper we study the role of social insurance, namely old-age pensions, disability insurance and healthcare, in accounting for the differing labor supply patterns of older individuals across OECD countries. To this end, we develop a life cycle model of labor supply and health with heterogeneous agents. The key features of the framework are: (1) people choose when to stop working, and when/if to apply for disability and pension benefits, (2) the awarding of disability insurance benefits is imperfectly correlated with health, and (3) people can partially insure against health shocks by investing in health, the cost of which is dependent on health insurance coverage. We find that the incentives faced by older workers differ hugely across countries. In fact, based solely on differences in social insurance programs, the model predicts even more cross-country variation in the employment rates of people aged 55-64 than we observe in the data.
Keywords: E24; J22; J26; 330; life cycle; retirement; disability insurance; health